Stable localized modes in asymmetric waveguides with gain and loss - Tsoy, Eduard N.; Allayarov, Izzat M.; Abdullaev, Fatkhulla (Optical Society of America, 2014)
It is shown that asymmetric waveguides with gain and loss can support a stable propagation of optical beams. This means that the propagation constants of modes of the corresponding complex optical potential are real. A class of such waveguides is found from a relation between two spectral problems. A particular example of an asymmetric waveguide, described by the hyperbolic functions, is analyzed. The existence and stability of linear modes and of continuous families of nonlinear modes are demonstrated.